Ultrasound-guided anterior iliopsoas muscle space block effectively reduces intraoperative hypotension in elderly adults undergoing hip surgery: A randomised controlled trial - Teng, Qingyu; Wang, Chengyu; Dong, Jing; Yan, Hai; Chen, Moxi; Xu, Tao (Frontiers in Molecular Neuroscience, 2023)
Background Hypotension often occurs during hip surgery in elderly adults with conventional posterior lumbosacral plexus block. Purpose We conducted a randomised controlled trial to determine if simple iliopsoas space block can lower the incidence of intraoperative hypotension (IOH) and provide sufficient perioperative pain relief during hip fracture surgery in elderly adults. Methods Patients undergoing surgery for elderly hip fracture were randomised to receive either an anterior iliopsoas space block with a lateral femoral cutaneous nerve block or a posterior lumbosacral plexus block. The primary outcome was a composite measure of IOH incidence comprising frequency, absolute and relative hypotension durations. Results Compared to the posterior group, the iliopsoas space block group had a decreased median frequency of IOH [1.09 (0-2. 14) vs. 3 (1.6-4.8), p=0.001, respectively] along with lower absolute [5 (0–10) min] and relative [minutes below systolic blood pressure of 100 mmHg in % of total anaesthesia time, 6.67 (0–7.65)] duration of IOH compared to the posterior group [35 (10–45) min, p = 0.008; 37.6 (12.99–66.18), p = 0.004, respectively]. The median pain levels in the post-anaesthesia care unit and median intraoperative sufentanil usage were comparable between the iliopsoas space group [2 (1–3); 8 (6–10) µg] and posterior group [1 (0–3); 5 (5–8) µg]. Thermal imaging revealed that the limb injected with the iliopsoas space block had a higher skin temperature than the unblocked limb in the sacral plexus innervated region. Conclusion A single iliopsoas space block lowers the IOH incidence and provides comparable perioperative analgesia to conventional lumbosacral plexus block. Trial registration www.chictr.org.cn (ChiCTR2100051394); registered 22 September 2021.